A healthy dose of realism: The role of optimistic and pessimistic expectations when facing a downward spiral in health. (July 2019) - Chipperfield, Judith G.; Hamm, Jeremy M.; Perry, Raymond P.; Parker, Patti C.; Ruthig, Joelle C.; Lang, Frieder R.
Abstract: Rationale and objectives: Whether expectations about future health are adaptive or maladaptive in late life likely depends on the extent to which they conform to or defy a future reality of declining health. Our premise was that, when adults face a downward spiral in health, it can be adaptive to realistically expect poorer future health and maladaptive to unrealistically expect good health. Method: This 18-year-long study of community-dwelling older Canadians ( n = 132, 72–98 years) involved a baseline interview to identify those who anticipated heath would decline (pessimistic expectation) or improve/remain stable (optimistic expectation). We determined initial (baseline) health status by assessing the severity of chronic conditions. An objective within-person measure of actual health change was derived by documenting hospital admissions (HAs) over time to capture a continuum that ranged from no declines (HAs remained stable) to greater declines in health (increasing numbers of HAs). Our a priori hypotheses examined the effects of health expectations (pessimistic, optimistic) and actual health change on the outcomes of depressive symptoms and mortality. Results: Support was found for our premise that it is adaptive to be realistic when forecasting future health, at least at low levels of initial chronic condition severity. Regression analyses showed that realistically pessimistic (vs. unrealistically optimistic) expectations predicted significantly fewer depressive symptoms and a lower risk of death. The results also supported our premise that it is maladaptive to be unrealistically optimistic when health subsequently declines in reality: The risk of death was 313% higher for those with optimistic expectations that were unrealistic (vs. realistic). Conclusion: These findings provide insights for health care professionals regarding the messages they communicate to their patients. Together, they imply that, when good health is slipping away, it seems optimal to encourage a healthy dose of realism. Highlights: Expectations about future health predict quality-of-life and mortality. It may be maladaptive to optimistically expect better health when it defies reality. It may be adaptive to pessimistically expect poorer health when it mirrors reality. A 313% higher risk of death for those with optimistic but unrealistic expectations. A healthy dose of realism seems optimal when good health is slipping away.